Sexual Practice and Perception of HIV/AIDS And Health Seeking Behaviour Among Men Who Have Sex with Men in Hyderabad - Krishna Nalla; Vijay kumar Maktha; Bhanuja Rani Bommi; Vinod Kumar Gokul (Medsci Publications, 2022)
Introduction: The Men who have Sex with Men (MSM) are a vulnerable population and need special attention in fight against the HIV/AIDS.  The HIV trend has been an increasing trend among MSM. Study was done to determine the factors influencing sexual practice, perception of HIV/AIDS and Health seeking behavior among MSM in Hyderabad. Methodology:  This was a facility based cross sectional study undertaken in the Targeted Intervention sites in Hyderabad, Telangana. A total of 300 Men who have Sex with Men who are above 18 years of age and registered were included. All the MSM visiting the TI centres during the study period were interviewed personally in their local language by using a pre-designed, pre-tested, semi structured and pre-coded proforma. Results: Mean age was 27.68 years. Majority of participants 119(39.66%) had their first sexual encounter at the age of 15-17 years. 130 (43.33%) visited the Target Intervention centres 1-2 times during the last month. About half of the participants i.e, 141(47.00%) belongs to Kothi Group and most of the MSM i.e, 198(66.00%) used condom during the sex with male last time. Conclusions: Stigma and cultural intolerance of same-sex relations are often largely to blame for rising epidemics, and until these issues are addressed it will be difficult to make  headway in reducing HIV infection levels among MSM - which, in turn, will hinder the wider global efforts to manage HIV and AIDS.